Aminoglycoside-Inactivating Enzymes in Clinical Isolates of Streptococcus Faecalis: AN EXPLANATION FOR RESISTANCE TO ANTIBIOTIC SYNERGISM - Krogstad, Donald J. (1978)
Clinical isolates of enterococci (Streptococcus faecalis) with high-level resistance to both streptomycin and kanamycin (minimal inhibitory concentration >2,000 μg/ml), and resistant to synergism with penicillin and streptomycin or kanamycin were examined for aminoglycoside-inactivating enzymes. All of the 10 strains studied had streptomycin adenylyltransferase and neomycin phosphotransferase activities; the latter enzyme phosphorylated amikacin as well as its normal substrates, such as kanamycin. Substrate profiles of the neomycin phosphotransferase activity suggested that phosphorylation occurred at the 3′-hydroxyl position, i.e., aminoglycoside 3′-phosphotransferase. A transconjugant strain, which acquired high-level aminoglycoside resistance and resistance to antibiotic synergism after mating with a resistant clinical isolate, also acquired both enzyme activities. Quantitative phosphorylation of amikacin in vitro by a sonicate of the transconjugant strain inactivated the antibiotic, as measured by bioassay, and the phosphorylated drug failed to produce synergism when combined with penicillin against a strain sensitive to penicillin-amikacin synergism. No differences were found in the sensitivity of ribosomes from a sensitive and resistant strain when examined in vitro using polyuridylic acid directed [(14)C]-phenylalanine incorporation in the presence of streptomycin, kanamycin, or amikacin. Therefore, we conclude that aminoglycoside-inactivating enzymes are responsible for the aminoglycoside resistance, and resistance to antibiotic synergism observed in these strains.